Soméah Culture as a Shaper of Brand Personality in Sundanese Ethnic Society: Implications of Personal Branding and Cultural Transactions - Ratnasari, Dewi; Sidiq, Fahmi; Kalfin (Communication in Research and Publications (CRP), 2023)
This research reviews the role of soméah culture in shaping the brand personality of the Sundanese people. Someméah reflects values such as friendliness, politeness, and openness which are reflected in daily communication behavior. The results showed that soméah culture influenced communication behavior, including the use of words such as